Thidiazuron aumenta a produtividade em arroz de terras altas1 - Alves, Cleiton José [UNESP]; Arf, Orivaldo [UNESP]; Garcia, Nayara Fernanda Siviero [UNESP]; Galindo, Fernando Shintate [UNESP]; Galassi, Arthur Dias [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2015)
The use of plant growth regulators in rice can provide reductions in plant height and decrease plant lodging. This study aimed at verifying the influence of the thidiazuron plant regulator on upland rice in the Brazilian Savannah region. The BRS Esmeralda and IAC 202 cultivars were used, as well as a randomized blocks design, in a 4 x 3 factorial arrangement for each cultivar, consisting of thidiazuron doses (0 g ha-1, 0.3 g ha-1, 0.6 g ha-1 and 0.9 g ha-1) and three application times (tillering, floral differentiation and booting), with four replications. The number of spikelets per panicle and spikelet fertility of the BRS Esmeralda cultivar were higher when using the thidiazuron dose of 0.9 g ha-1 in the tillering stage. The weight of 100 grains of the BRS Esmeralda cultivar fitted a quadratic equation, while the IAC 202 fitted a linear equation, with the best time of application taking place during the tillering stage. For hectoliter weight, the results for the BRS Esmeralda also fitted a quadratic equation, while for the IAC 202 a significant difference was observed only among times, being the booting stage the best application time. Grain yield fitted a positive linear equation for both the BRS Esmeralda and IAC 202 cultivars, with gains of 23.5 % and 6.5 %, respectively, when compared to the control. Thidiazuron positively influences grain yield for upland rice.

A utilização de reguladores vegetais em arroz pode proporcionar redução na altura de plantas e diminuir o acamamento. Objetivou-se verificar a influência da aplicação do regulador vegetal thidiazuron na cultura do arroz de terras altas, em região de Cerrado brasileiro. Utilizaram-se as cultivares BRS Esmeralda e IAC 202, bem como delineamento experimental de blocos casualizados, em esquema fatorial 4 x 3 para cada cultivar, constituído de doses de thidiazuron (0 g ha-1; 0,3 g ha-1; 0,6 g ha-1; e 0,9 g ha-1) e três épocas de aplicação (perfilhamento, diferenciação floral e emborrachamento), com quatro repetições. O número de espiguetas por panícula e fertilidade das espiguetas da cultivar BRS Esmeralda foram maiores utilizando-se a dose de 0,9 g ha-1 de thidiazuron, com aplicação na fase de perfilhamento. A massa de 100 grãos da BRS Esmeralda se ajustou a uma equação quadrática, enquanto, para a IAC 202, houve ajuste a uma equação linear, com melhor época de aplicação durante o perfilhamento. Para massa hectolítrica da BRS Esmeralda, os resultados também se ajustaram a uma equação quadrática, enquanto, para a IAC 202, houve diferença significativa apenas entre as épocas, sendo o emborrachamento a melhor época de aplicação. As produtividades de grãos da BRS Esmeralda e IAC 202 apresentaram ajuste linear positivo, com ganhos de 23,5 % e 6,5 %, respectivamente, em relação à testemunha. O thidiazuron influencia positivamente na produtividade da cultura do arroz de terras altas.
Thidiazuron increases upland rice yield
Keywords: Oryza sativa L.; plant regulator; cytokinin; Oryza sativa L.; regulador vegetal; citocinina